Evaluasi Penggunaan Antibiotik Pada Pasien Infeksi Saluran Pernapasan Akut Atas (ISPAa) Di Instalasi Rawat Jalan Rumah Sakit X: Evaluation of Appropriate Antibiotic Use in Patients with Acute Upper Respiratory Tract Infections (AURTIs) at the Outpatient Department of Hospital X - Lailla Shafia; Dina melia oktavilantika (Universitas Gunadarma, 2026)
Acute Upper Respiratory Tract Infection (AURTI) is a disease caused by an acute infection affecting the upper respiratory tract, typically resulting from bacteria and viruses. According to the 2018 Riskesdas report from the DKI Jakarta province, AURTI is among the most common infectious diseases in Jakarta, with a prevalence of 8.49%. The data indicates that AURTI is a recurring health issue each year, with several factors contributing to the rising incidence, one of which is irrational treatment. This study aims to determine the pattern of antibiotic use and the rationality of antibiotic use in AURTI therapy. This research is a non-experimental study with retrospective data collection and descriptive data analysis. The results show that the most commonly used antibiotics were cefixime (67%), azithromycin (14%), amoxicillin-clavulanate (8%), clindamycin (6%), amoxicillin (4%), and levofloxacin (2%), with oral administration. Of the 51 AURTI patient records evaluated in the Outpatient Department, the results showed 100% appropriateness in patient selection, 100% appropriateness in indication, 39% appropriateness in drug selection, 100% appropriateness in dosage, 96% appropriateness in duration, 94% appropriateness in frequency and route of administration 100%.